2005
DOI: 10.1038/sj.emboj.7600915
|View full text |Cite
|
Sign up to set email alerts
|

A subcomplex of RNA polymerase III subunits involved in transcription termination and reinitiation

Abstract: While initiation of transcription by RNA polymerase III (Pol III) has been thoroughly investigated, molecular mechanisms driving transcription termination remain poorly understood. Here we describe how the characterization of the in vitro transcriptional properties of a Pol III variant (Pol IIIdelta), lacking the C11, C37, and C53 subunits, revealed crucial information about the mechanisms of Pol III termination and reinitiation. The specific requirement for the C37-C53 complex in terminator recognition was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
222
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(244 citation statements)
references
References 38 publications
21
222
1
Order By: Relevance
“…1B, lanes 3-5). In contrast to this apparent inability of Pol III to incorporate a mispaired nucleotide, Chédin et al (25) have reported that transcription of SUP4 in the absence of GTP by Pol III⌬, an incomplete form of Pol III lacking the C11, C37 and C53 subunits, resulted in formation of an 18-mer transcript differing at the 3Ј end from the 17-mer produced by Pol III (25,26). The authors suggested that Pol III⌬ incorporated a mispaired nucleotide at position ϩ18, which failed to be subsequently removed because of the lack of RNAcleavage activity in Pol III⌬ resulting from the absence of the TFIIS-like C11 subunit (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B, lanes 3-5). In contrast to this apparent inability of Pol III to incorporate a mispaired nucleotide, Chédin et al (25) have reported that transcription of SUP4 in the absence of GTP by Pol III⌬, an incomplete form of Pol III lacking the C11, C37 and C53 subunits, resulted in formation of an 18-mer transcript differing at the 3Ј end from the 17-mer produced by Pol III (25,26). The authors suggested that Pol III⌬ incorporated a mispaired nucleotide at position ϩ18, which failed to be subsequently removed because of the lack of RNAcleavage activity in Pol III⌬ resulting from the absence of the TFIIS-like C11 subunit (25).…”
Section: Resultsmentioning
confidence: 99%
“…The SUP4 gene was transcribed in the absence of GTP by Pol III⌬ preincubated with the recombinant C11 subunit (rC11). The resulting halted ternary complexes contained a 17-mer RNA and were purified to remove rC11 and the NTPs (25,26). Traces of the 18-mer transcript remained, which could be attributed to a somewhat reduced cleavage efficiency of rC11 compared with the endogenous C11, and a negligible amount of a slippage product (27) was observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro transcription using RNAPIII lacking the RNA-PIII-specific subunits C11, C37, and C53 (RNAPIIID) can support transcription initiation but fails to terminate properly (Landrieux et al 2006). Adding back the heterodimer C37/C53 was sufficient to allow recognition of the terminator and to correct the termination defect, but not for transcription reinitiation.…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 99%
“…Landrieux et al (2006) showed that C11 RNA cleavage activity is not required for correct recognition of the RNAPIII terminator elements and release of the newly synthesized transcript. However, C11 itself, but not its cleavage activity, is required for reinitiation (Chedin et al 1998;Landrieux et al 2006). These experiments strongly suggest that termination and cleavage of the RNA precursor are not coupled in the RNAPIII transcription process.…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 99%
See 1 more Smart Citation